Kinerja Simpang Punge Blang Cut Kota Banda Aceh Menggunakan Metode MKJI dan Vissim - M Isya; Yusria Darma; Sugiato Sugiarto; Rachmat Taufiqy; Aidil Ambiya Zula (Universitas Teuku Umar, 2020)
ABSTRACTThe Punge Blang Cut intersection in the city of Banda Aceh is a four-armed unsignalised intersection. The location of this intersection is on Jl. Sultan Iskandar Muda, where this road connects the city center to the west side of the city to the Ulee Lheue port. The west to east road direction is a major road and the north to south direction is a minor road. On the west arm there is two lane at each direction with a median, and at the east side there is two lane and two direction with a bridge by length of 20m and whithout median. On the north and south arms side there is a slight incline. Especially at the south side arm is not perpendicular to major line road. At this recent time it is estimated that traffic performance should be at a low level and of course it will be even lower in the future. For this reason, it is necessary to evaluate the traffic performance of the intersection for handling purposes in the future. At the beginning of conducting this research, data needed were: volume and compotition of traffic, intersection geometric, environmental conditions and secondary data as support. Data processing was carried out based on the Indonesian Road Capacity Manual (MKJI) 1997 and Vissim methods.